Humanoid Nurse Robots and Compassion: Dialogical Conversation with Rozzano Locsin - Trecella May Macalam; Rozzano Locsin (San Beda University, 2020)
It is important that in the future, nursing practice is framed with the humanoid nurse robot (HNR) functionality as a sure partner capable of expressing compassion that mimics human persons. Sr. Trecella May Macalam, SPC, a member of the Sisters of St. Paul of Chartres congregation, and doctoral student of St. Paul University Philippines and Dr. Rozzano Locsin, nurse theorist and author of the theory of Technological Competency as Caring in Nursing (TCCN) discuss the futurist idea of HNR's capability to express compassion in nursing. Locsin's theory has inspired the utility of advancing machine technologies in health care practice. Framing explanations and descriptions between human persons and HNRs as intelligent healthcare robots (IHRs) stimulate future nursing care in many ways. The theory of TCCN inspired "knowing persons as caring" as a process of nursing. In the future, this theory will most likely influence the inevitability and dependency of nursing through compassion in nursing by HNRs.